Obstetric and neonatal outcome of ART in patients with polycystic ovary syndrome: IVM of oocytes versus controlled ovarian stimulation. Issue 8 (26th July 2019) - Mostinckx, L; Segers, I; Belva, F; Buyl, R; Santos-Ribeiro, S; Blockeel, C; Smitz, J; Anckaert, E; Tournaye, H; De Vos, M
ABSTRACT: STUDY QUESTION: Does IVM of immature oocytes retrieved from small antral follicles in women with polycystic ovary syndrome (PCOS) have an impact on obstetric and neonatal outcomes compared to controlled ovarian stimulation (COS)? SUMMARY ANSWER: Obstetric and neonatal outcomes after IVM appear to be similar to those after COS. WHAT IS KNOW ALREADY: Women with PCOS have an increased risk of adverse pregnancy outcomes and congenital malformations in their offspring. For patients with PCOS who require IVF, IVM of germinal vesicle (GV)-stage oocytes retrieved from antral follicles has been adopted as a mild approach ART, with improved pregnancy rates over the last two decades. Although reports of obstetrical and neonatal outcomes after IVM have been reassuring, the limited sample sizes in previous studies preclude firm conclusions, and further study is warranted. STUDY DESIGN, SIZE, DURATION: This is a retrospective observational study analysing obstetric and neonatal data from 1036 clinical pregnancies in unique patients with PCOS who conceived following a cycle of IVM or COS between January 2010 and December 2016 in a tertiary reproductive centre. In total, 393 singleton pregnancies with a gestational age beyond 20 weeks were included. A phenotypic approach was used for the diagnosis of PCOS. Pregnancies following oocyte donation, standard IVF (as opposed to ICSI) or preimplantation genetic testing and pregnancies requiring testicular biopsy in the male partners were excluded. PARTICIPANTS/MATERIALS, SETTING, METHODS: Pregnancy outcomes were analysed in women with PCOS phenotype A, C or D, as defined by different combinations of the Rotterdam criteria. Data from 164 pregnancies beyond 20 weeks after IVM were compared with those from 229 pregnancies after COS. Pregnancies in the IVM group were obtained after minimal ovarian stimulation and IVF with ICSI of transvaginally collected GV oocytes that had reached the metaphase II stage in vitro after 28 to 40 h of culture. No hCG trigger was administered before oocyte retrieval. Outcome measures were analysed or reported in singleton pregnancies only and included adverse obstetric events and neonatal health parameters, in particular birthweight, prematurity, small-for-gestational age, large-for-gestational age, perinatal death and major/minor malformation rates. The incidence of hypertensive disorders of pregnancy (HDP) and birthweight was analysed by multiple linear and logistic regression, adjusted for relevant treatment variables and maternal characteristics. MAIN RESULTS AND THE ROLE OF CHANCE: The IVM and the COS groups differed significantly ( P < 0.001) for maternal circulating AMH levels and PCOS phenotype distribution, with more of the PCOS phenotype A in the IVM group. Pregnant women in the IVM group were younger than pregnant women in the COS group ( P = 0.05). With regard to obstetric complications in singleton pregnancies, in the unadjusted analysis, mothers of infants in the IVM group more often had HDP (29/164 (17.9%) vs 22/229 (9.6%), P = 0.02) compared with mothers in the COS group. Singletons born after IVM and COS had a similar birthweight standard deviation score (SDS) (0.51 ± 0.94 after IVM vs 0.33 ± 1.05 after COS, P = 0.19). Preterm birth rate (32–36.9 weeks) and early preterm birth rate (<32 weeks) were also similar in both groups. The total malformation rate was 4.1% in singletons after IVM and 2.4% in singletons after COS. Multivariate linear regression analysis accounting for relevant confounders demonstrated that parity was the only independent predictive factor ( P = 0.04) for birthweight SDS. Multivariate logistic regression analysis showed that BMI, parity and type of ART (IVM as opposed to COS) were significantly correlated with the incidence of HDP. Only patients with the PCOS phenotype A showed a tendency towards a higher risk of HDP in those who underwent IVM compared to those who had COS. LIMITATIONS, REASONS FOR CAUTION: The study is limited by its retrospective nature and loss to follow-up of a subset of children with no information regarding congenital malformations. Furthermore, the paediatricians who assessed the children after birth were not blinded for the type of ART procedure. WIDER IMPLICATIONS OF THE FINDINGS: This study provides further evidence that, compared to COS, IVM of oocytes derived from small antral follicles does not adversely affect the neonatal health of the offspring of patients with PCOS. The observed increased risk of HDP in patients with PCOS phenotype A following IVM treatment warrants further scrutiny. STUDY FUNDING/COMPETING INTEREST(S): Translational IVM research at Universitair Ziekenhuis Brussel (UZ Brussel) and Vrije Universiteit Brussel (VUB) has been supported by grants from the Institute for the Promotion of Innovation by Science and Technology in Flanders (Agentschap voor Innovatie door Wetenschap en Technologie—IWT, project 110680), the Fund for Research Flanders (Fonds Wetenschappelijk Onderzoek–Vlaanderen—FWO, project G.0343.13) and the Belgian Foundation Against Cancer (HOPE project, Dossier C69). Clinical IVM research was supported by research grants from Cook Medical and Besins Healthcare. M.D.V. reports honoraria for lectures from Cook Medical and Besins Healthcare outside the submitted work. S.S.R. reports honoraria for lectures by MSD and Besins and research grants by MSD, Ferring and Merck Serono outside of the submitted work. C.B. reports personal fees from Merck-Serono, Ferring, IBSA, Finox, MSD and Abbott outside the submitted work. H.T. reports grants from Merck, MSD, Goodlife, Cook, Roche, Besins, Ferring, Mithra (now Allergan) and the Research Fund of Flanders (FWO) and consultancy fees from Finox, Abbott, Obseva and Ovascience outside the submitted work. The other authors have nothing to disclose.